Analisis Vegetasi Tingkat Tiang dan Pohon di Bukit Mandiangin KHDTK ULM Provinsi Kalimantan Selatan - Anshari, Adi; Peran, Setia Budi; Susilawati, Susilawati (Jurnal Sylva Scienteae, 2024)
Vegetation diversity is one of the important aspects in plant ecology that affects ecosystem stability and environmental health. Vegetation diversity has important impacts on ecosystem functions, including nutrient cycling, carbon sequestration, soil protection, and ecosystem recovery after disturbance One place that stores a variety of vegetation in South Kalimantan is Mandiangin hill located in South Kalimantan Province, area  107,036 ha as miniature tropical rainforest stands. The abundance of various types of forest vegetation needs to be analyzed to determine the structure and composition of the forest. This research was conducted in order to analyze the type, composition, diversity, evenness and dominance of vegetation types at the pole level in Bukit Mandiangin KHDTK ULM. The research method in taking data on the composition and structure of vegetation on Mandingan hill was carried out through vegetation analysis activities using the Line Intercept Method with an observation plot size of 10×10 m for pole-level vegetation analysis. The results showed that there were 17 types of pole level identification with a total of 116 individuals. The highest pole-level vegetation structure is found in the Madang puspa type with INP 53.50%, Marsihung 50.73%, Tarap 34.11%, Alaban 30.29% and Jamai 26.09%. The diversity of vegetation types in Bukit Mandiangin is based on the analysis of the diversity value index (H') at the pole level with 2.47 which means it has medium criteria. Type evenness based on the analysis of the type evenness index (e) pole level 0.87 with almost even criteria. Dominance is based on the analysis of the dominance index (c) pole level 0.10 which means it has low criteria.Keanekaragaman vegetasi merupakan salah satu aspek penting dalam ekologi tumbuhan yang mempengaruhi stabilitas ekosistem dan kesehatan lingkungan. Keanekaragaman vegetasi memiliki dampak penting terhadap fungsi ekosistem, termasuk siklus nutrisi, penyerapan karbon, perlindungan tanah, dan pemulihan ekosistem setelah gangguan Salah satu tempat yang menyimpan berbagai vegetasi yang berada di Kalimantan Selatan ialah bukit Mandiangin yang terletak di Provinsi Kalimantan Selatan, luasan  107,036 ha  sebagai miniatur tegakan hutan hujan tropis. Banyaknya berbagai jenis vegetasi hutan perlu dianalisis untuk mengetahui struktur dan komposisi hutan. Penelitian ini dilakukan dalam guna menganalisis jenis, komposisi, keanekaragaman, kemerataan serta dominansi jenis vegetasi pada tingkat tiang di Bukit Mandiangin KHDTK ULM. Metode penelitian dalam pengambilan data komposisi dan struktur vegetasi dibukit Mandingan dilakukan melalui kegiatan analisis vegetasi dengan mengggunakan metode garis berpetak (Line Intercept Method) dengan ukuran petak pengamatan 10×10 m untuk analisis vegetasi tingkat tiang. Hasil penelitian menunjukan bahwa identifikasi tingkat tiang terdapat 17 jenis dengan jumlah sebanyak 116 individu. Struktur vegetasi tingkat tiang paling tinggi terdapat pada jenis Madang puspa dengan INP 53,50%, Marsihung 50,73%, Tarap 34,11%, Alaban 30,29% dan Jamai 26,09%. Keanekaragaman jenis vegetasi di Bukit Mandiangin berdasarkan analisis indeks nilai keragaman (H’) tingkat tiang dengan 2,47 yang berarti memiliki kriteria sedang. Kemerataan jenis berdasarkan analisis indeks kemerataan jenis (e) tingkat tiang 0,87 dengan kriteria hampir merata. Dominansi berdasarkan analisis indeks dominansi (c) tingkat tiang 0,10 yang mengartikan memiliki kriteria rendah.